Diffusion of Innovation in Sustainable Development Projects: A Proposed Integrative Model - Hassan, Afaf (Environmental Management and Sustainable Development, 2022)
To support an effective diffusion of innovations (DOI) in sustainable development (SD) projects, this paper presents a research-based integrative model to illustrate the factors leading the process of diffusion of innovation to succeed or fail in sustainable development projects. The proposed integrative model is based on diffusion of innovation principles founded in the research of Everett Rodgers that emphasizes the process of an effective innovation diffusion. Special emphasis is placed on determining not only the success factors for adequate innovation diffusion, but also on enabling a successful adoption to take place. Key finding obtained from the proposed integrative model is that there are three main stages for adopting DOI in SD projects that are creation of innovative ideas in SD projects, DOI ideas in SD projects, and adoption of innovative ideas in sustainable development projects. Each one of these stages leads to two possibilities that are the success or failure of that stage, depending of the fulfillment of the suggested factors for each option. In brief, the suggested integrated model proposes that the DOI in SD projects will succeed if the three core stages meet the success factors.